Silicon: A valuable soil element for improving plant growth and CO2 sequestration - Abdul Latif Khan (Journal of Advanced Research)
Background: Silicon (Si), the second most abundant and quasi-essential soil element, is locked as a recalcitrant silicate mineral in the Earth’s crust. The physical abundance of silicates can play an essential role in increasing plant productivity. Plants store Si as biogenic silica (phytoliths), which is mobilized through a chemical weathering process in the soil. Aim of review: Although Si is a critical element for plant growth, there is still a considerable need to understand its dissolution, uptake, and translocation in agroecosystems. Here, we show recent progress in understanding the interactome of Si, CO2, the microbiome, and soil chemistry, which can sustainably govern silicate dissolution and cycling in agriculture. Key scientific concepts of this review: Si cycling is directly related to carbon cycling, and the resulting climate stability can be enhanced by negative feedback between atmospheric CO2 and the silicate uptake process. Improved Si mobilization in the rhizosphere by the presence of reactive elements (for example, Ca, Na, Al, Zn, and Fe) and Si uptake through genetic transporters in plants are crucial to achieving the dual objectives of (i) enhancing crop productivity and (ii) abiotic stress tolerance. Furthermore, the microbiome is a symbiotic partner of plants. Bacterial and fungal microbiomes can solubilize silicate minerals through intriguingly complex bioweathering mechanisms by producing beneficial metabolites and enzymes. However, the interaction of Si with CO2 and the microbiome’s function in mobilization have been understudied. This review shows that enhancing our understanding of Si, CO2, the microbiome, and soil chemistry can help in sustainable crop production during climatic stress events.